Nexus between Government Assistance and Savings: Preliminary Analysis of Households in Malaysia - Mohd Shakil, Nurul Syifaa; Mohamad Azhar, Nur Azirah Zahida; Othman, Norashida; Zainuddin, Ahmad Zuhairi; Rachmawati, Lucky; Aji, Tony Seno; Cahyono, Hendry (Information Management and Business Review, 2023)
This preliminary study investigates the relationship between government assistance and household savings. The study aimed to shed light on whether government assistance programs directly influence households’ savings habits. Data were collected from 25 representative sample households, including their income, expenses, savings, and participation in government assistance programs. The study examined how much money households could save regularly. The study suggested a significant correlation, between government assistance and household savings. Families that received some form of government support demonstrated a lower propensity to save than those who did not receive assistance. This trend was consistent across different income brackets and demographic groups. The researchers proposed several potential reasons for this relationship. There can be several reasons for this negative relationship. First, increased government assistance may alleviate financial strain and provide immediate relief for individuals or households, reducing the urgency or perceived need to save for future expenses or emergencies. Second, some government assistance programs may have income limits or asset tests that discourage or restrict saving behavior. It is important to note that this study was preliminary, and further research is necessary to establish a more robust understanding of the relationship between government assistance and household savings. Future studies could delve into the long-term effects of government support on savings behavior and investigate the specific mechanisms through which assistance programs influence savings habits. The preliminary findings suggest a negative association between government assistance and household savings. It emphasizes the importance of further exploring this relationship to understand household financial well-being comprehensively.